Biomedical applications of nanomaterials: A short review - Durmuş, Hüseyin Okan (Nano and Medical Materials, 2024)
Nanomaterials have emerged as transformative tools in the biomedical field due to their distinct physical and chemical properties. This review delves into the synthesis, classifications, and applications of nanomaterials, emphasizing advancements in drug delivery, bioimaging, and diagnostics. Unique aspects include a focused discussion on sol-gel synthesis methods and recent trends in nanomaterial applications for personalized medicine. The review concludes with a future perspective on overcoming challenges such as toxicity and regulatory issues, paving the way for sustainable biomedical innovations.